2019
DOI: 10.1002/jaba.564
|View full text |Cite
|
Sign up to set email alerts
|

Comparing mand training and other instructional methods to teach a foreign language

Abstract: The purpose of the current study was to examine the effects of mand, tact, and native‐to‐foreign (NFI) and foreign‐to‐native (FNI) intraverbal training on the acquisition of a foreign language. We used a multiple‐baseline design across participants with an embedded adapted alternating treatments design to compare the effects of mand training, tact training, NFI training, and FNI training on the acquisition rate of Chinese words in four typically developing adults. We also examined the emergence of untrained fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(45 citation statements)
references
References 16 publications
4
34
0
6
Order By: Relevance
“…Second, future research should explore the role of preference for stimuli on the acquisition of a foreign language repertoire. W. L. Wu et al (2019) suggested that teaching mands in a foreign language may be more efficient than teaching tacts or intraverbals, likely due to the motivational variables (Michael & Miguel, 2020) present during instruction. If motivational variables play an important role in learning a foreign language, then future research should manipulate these variables when teaching tacts and intraverbals (e.g., by teaching participants to tact preferred objects, or letting participants choose the topic of the conversation).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, future research should explore the role of preference for stimuli on the acquisition of a foreign language repertoire. W. L. Wu et al (2019) suggested that teaching mands in a foreign language may be more efficient than teaching tacts or intraverbals, likely due to the motivational variables (Michael & Miguel, 2020) present during instruction. If motivational variables play an important role in learning a foreign language, then future research should manipulate these variables when teaching tacts and intraverbals (e.g., by teaching participants to tact preferred objects, or letting participants choose the topic of the conversation).…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing body of literature examining the effectiveness of teaching a foreign language using behavior‐analytic procedures (Cortez et al, 2020; Daly & Douvani, 2020; Davidson & O'Connor, 2019; Dounavi, 2011, 2014; Matter et al, 2020; May et al, 2016, 2019; Petursdottir & HafliĐadóttir, 2009; Petursdottir et al, 2008; Rosales et al, 2012; H. Wu & Miller, 2007; W. L. Wu et al, 2019). Overall, these studies focused on teaching a subset of skills (e.g., listener and tact responses) and probing the emergence of others (e.g., intraverbal responses) to evaluate the most effective and efficient arrangements.…”
mentioning
confidence: 99%
“…(2016) and Jennings and Miguel (2017) used tact and intraverbal training to establish equivalence classes. Additionally, three experiments compared intraverbal training to tact training (6.1%; Daly & Dounavi, 2020; Maldonado et al., 2020; Wu et al., 2019). Nearly one third of experiments (29.2%) investigated the intraverbal as the dependent variable.…”
Section: Resultsmentioning
confidence: 99%
“…Researchers should also evaluate procedures to teach mands for information to other populations. For example, if a child has a fully developed verbal behavior repertoire in one language, it is possible to only need to teach them to tact an item in the other language for the other verbal operants to emerge (i.e., derived relational responding; see Wu et al., 2019). In contrast, there are individuals with developmental disabilities who cannot communicate vocally.…”
Section: Discussionmentioning
confidence: 99%